MEDICAL INSTRUMENT: IMPORTANCE, TYPES, AND APPLICATIONS (International journal of artificial intelligence, 2025)
Medical instruments are fundamental tools that assist healthcare professionals in diagnosing,monitoring,and treating patients.This article explores the importance ,classification,and technological progress of medical instruments.It also emphasizes how innovation in medical devices improves accuracy,safety,and efficiency in heathcare delivery.Furthermore,the paper discusses the importance of sterilization and proper maintenance to ensure patient safety and the longevity of instruments.